각가속도를 이용한 이족 로봇의 동적 걸음새 구현 - 박재문; 박승엽; 고봉진; Park, Jae-Mun; Park, Seung-Yub; Ko, Bong-Jin (한국항행학회논문지, 2007)
In this paper, we embodied posture-stabilization and dynamic gait in a walking robot. 10 RC servo motors are used to operate joints. And the joints have enough moving ranges suitable in any walking pattern. Each joint trajectory is generated by cubic spline interpolation method and the stability of the trajectory is verified by using Zero Moment Point from the robot modeling. To avoid complex structure and expression, Zero Moment Point of the biped robot used angular acceleration is suggested. To measure the stability of the biped robot, Tilt sensor and gyro sensor are used. Finally, Personal Computer is used computer monitoring and data processing. Most of computation, such as 10 RC servo motor control, joint trajectory generating, ZMP compensation, sense measuring, etc, was used Digital Signal Processor. 본 논문에서는 보행 로봇의 자세 안정화 및 동적 걸음새를 구현하였다. 10개의 RC 서보모터가 로봇 관절에 사용되었고, 각 로봇의 관절은 어떤 걸음새 동작에도 충분히 움직일 수 있게 하였다. 각 관절 궤적은 3차 스플라인 보간법에 의해 생성되며, 궤적의 안정성은 로봇 모델링에 의한 ZMP(Zero Moment Point)를 이용하여 입증하였다. 또한 복잡한 구조와 표현을 피하기 위해 각 가속도를 이용한 ZMP방법을 구현 하였고, 로봇의 안정 상태를 측정하기 위해 기울기 센서와 자이로 센서가 사용되었다. 10개의 서보모터 제어, 궤적 생성, ZMP 보상, 센서 측정 등 과 같은 대부분의 계산 과정은 DSP에서 이루어지며, PC에서는 단순히 로봇의 상태, 데이터 처리 등의 모니터링에 이용하였다.